MSC-Derived Extracellular Vesicle-Delivered L-PGDS Inhibit Gastric Cancer Progression by Suppressing Cancer Cell Stemness and STAT3 Phosphorylation - Benshuai You; Can Jin; Jiaxin Zhang; Min Xu; Wenrong Xu; Zixuan Sun; Hui Qian (Stem Cells International)
Mesenchymal stem cell- (MSC-) derived extracellular vesicles (EVs) serving as delivery system have attracted extensive research interest, especially in cancer therapy. In our previous study, lipocalin-type prostaglandin D2 synthase (L-PGDS) showed inhibitory effects on gastric cancer growth. In this study, we aimed to explore whether MSC-EV-delivered L-PGDS (EVs-L-PGDS) could inhibit gastric cancer progression. EVs-L-PGDS were generated from MSCs transfected with adenovirus encoding L-PGDS. Cell colony-forming, migration, invasion, and flow cytometry assays were used to show the inhibitory effects of EVs on tumor cells in vitro, and the nude mouse subcutaneous tumor model was performed to show the inhibitory effect of EVs on tumor progression in vivo. In vitro, EVs-L-PGDS could be internalized and inhibit the colony-forming, migration, and invasion ability of gastric cancer cell SGC-7901 and promote cell apoptosis. In vivo, EVs-L-PGDS inhibited the tumor growth in nude mouse subcutaneous tumor-bearing model. Compared with the PBS and EVs containing empty vector (EVs-Vector) group, more apoptotic cells and higher L-PGDS expression were detected in tumor tissue of the EVs-L-PGDS treatment group. And these differences are significant. Mechanistically, EVs-L-PGDS reduced the expression of stem cell markers including Oct4, Nanog, and Sox2 and inhibited STAT3 phosphorylation in gastric cancer cell SGC-7901. In conclusion, our results imply that MSC-derived EVs could be utilized as an effective nanovehicle to deliver L-PGDS for gastric cancer treatment, which provides a novel idea for the EV-based cancer therapy.